Social Commerce Adoption in SMEs - Zamrudi, Zakky; Wicaksono, Teguh (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
Small and medium enterprises (SMEs) has gradually become an economic backbone for several developing country including Indonesia. In several studies, it was assumed that SMEs was a sign of self-sufficiency concept. In the economic strike, SME's could sustain the price of several staple goods that are related to society livelihoods such as food and attire. South Kalimantan Province was well known for its authentic fabric namely sasirangan produced by local SME's spread all around the area. SMEs are nowadays are inseparable from IT particularly that related to social media to promote their product. The use of IT infrastructure and platform were usually centered in the large city mainly in the capital of province such as Banjarmasin. As an alternative, the use of social media could be employed to empower SMEs at county area. This study was aimed to understand the attitude of county area SMEs on the use of social media for commerce purposes. The sample involved in this study was 45 Sasirangan SMEs on 5 off-capital counties at South Kalimantan Province. These works use PLS-SEM due to the nature of research was explore the interaction amongst the variable (exploratory factor analysis). The finding shows that in general, SMEs entrepreneur has a great willingness to use their social media for commerce purposes. A further discussion of research finding and research limitation will be further discussed in the end of paper.